Highly Unsaturated Fatty Acid Synthesis in Atlantic Salmon: Characterization of ELOVL5- and ELOVL2-like Elongases - Morais, Sofia; Monroig, Oscar; Zheng, Xiaozhong; Leaver, Michael; Tocher, Douglas R (Marine Biotechnology, 2009)
Fish species vary in their capacity to biosynthesize the n-3 long-chain polyunsaturated fatty acids (LC-PUFA) eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids that are crucial to the health of higher vertebrates. The synthesis of LC-PUFA involves enzyme-mediated fatty acyl desaturation and elongation. Previously, a cDNA for an elongase, now termed elovl5a, had been cloned from Atlantic salmon. Here we report on the cloning of two new elongase cDNAs: a second elovl5b elongase, corresponding to a 294 aa protein, and an elovl2-like elongase, coding for a 287 aa protein, characterized for the first time in a non-mammalian vertebrate. Heterologous expression in yeast showed that the salmon Elovl5b elongated C18 and C20 PUFA, with low activity towards C22, while Elovl2 elongated C20 and C22 PUFA with lower activity towards C18 PUFA. All three transcripts showed predominant expression in the intestine and liver, followed by the brain. Elongase expression showed differential nutritional regulation. Levels of elovl5b and particularly of elovl2, but not of elovl5a, transcripts were significantly increased in liver of salmon fed vegetable oils (VO) compared to fish fed fish oil (FO). Intestinal expression showed a similar pattern. Phylogenetic comparisons indicate that, in contrast to salmon and zebrafish, Acanthopterygian fish species lack elovl2 which is consistent with their neglible ability to biosynthesise LC-PUFA and to adapt to VO dietary inclusion, compared to predominantly freshwater salmonids. Thus the presence of elovl2 in salmon explains the ability of this species to biosynthesise LC-HUFA and may provide a biotechnological tool to produce enhanced levels of LC-PUFA, particularly DHA, in transgenic organisms.